Every Caesarean Section Must Count. Issue 3 (September 2017) - Ellwood, D.; Oats, J.
Abstract : ( Aust N Z J Obstet Gynaecol. 2016;56(5):450–452) This opinion piece supports the argument that cesarean section rates (CSR) are an essential indicator of the quality of care and should be monitored. Between 1985 and 2013 the CSR increased from 15% to 32.8%—more than a doubling in <3 decades. Arguments against the monitoring of CSR include the rights of women to opt for the procedure, high intrapartum stillbirth rates, and the preventable burden of lifelong disabilities caused by intrapartum asphyxia and perineal lacerations resulting from vaginal deliveries. Yet, the risks associated with cesarean section (CS) and the potential morbidity as a result of an increased CSR support making sure each CS is indicated.